Challenges of AI-Empowered Foreign Language Teaching and Human–AI Co-Teaching Pathways from the Perspective of Embodied Cognition - Liu, Xinyu (Journal of Educational Research and Policies, 2026)
The integration of artificial intelligence (AI) is profoundly reshaping foreign language teaching. While offering instant feedback and personalized resources, it also creates tensions between “disembodied” technological rationality and the “embodied” goals of education. From the perspective of embodied cognition, this study examines key dilemmas in AI-empowered teaching, including the marginalization of bodily experience, AI’s limitations in emotional understanding and cultural aesthetics, and the crisis of subjectivity caused by imbalanced human–machine relations. This study argues that language acquisition is fundamentally an embodied process, emerging from the interaction among the cognitive subject, the body, space, and the environment. It therefore proposes a human–AI co-teaching model, in which collaborative knowledge construction enables functional complementarity, role reconfiguration, and shared responsibility. By leveraging AI while preserving teachers’ central role in contextual design and emotional guidance, this model seeks to restore the embodied nature of language teaching grounded in social interaction and practical use.